2022
DOI: 10.21123/bsj.2022.19.1.0055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endothelin-I and A symmetric Dimethylarginine Levels with Insulin Resistance in Type-2 Diabetes Mellitus Patients

Abstract: Endothelin-I (ET-I) is one of the potent vasoconstrictors secreted from endothelial cells when needed. Many studies revealed the elevation of serum ET-I with human diabetes and microangiopathies. Since insulin resistance is a case of mixed diabetic and pre-diabetic cases, many risk factors beyond obesity and inflammation are proposed. The current study aims to demonstrate the association between serum ET-I and asymmetric dimethylarginine (ADMA) and insulin resistance in type 2 diabetes mellitus (T2DM). Sera of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Connective tissue growth factor (CTGF) expression is modest in healthy adult kidneys but is significantly elevated in a number of renal disorders, where it plays an important role in the development of glomerular and tubular interstitial fibrosis involved in cell migration, proliferation and differentiation, connective tissue growth factor (CTGF) acts either directly to promote fibrosis 39 .Our current study demonstrated an increase in connective tissue growth factor, which indicates glomerular and tubular damage and fibrosis in diabetic patients. This finding is consistent with Koszegi, S., et al who found elevated serum connective tissue growth factor (CTGF) expression as a strong predictor of renal fibrosis 40 .…”
Section: Discussionsupporting
confidence: 91%
“…Connective tissue growth factor (CTGF) expression is modest in healthy adult kidneys but is significantly elevated in a number of renal disorders, where it plays an important role in the development of glomerular and tubular interstitial fibrosis involved in cell migration, proliferation and differentiation, connective tissue growth factor (CTGF) acts either directly to promote fibrosis 39 .Our current study demonstrated an increase in connective tissue growth factor, which indicates glomerular and tubular damage and fibrosis in diabetic patients. This finding is consistent with Koszegi, S., et al who found elevated serum connective tissue growth factor (CTGF) expression as a strong predictor of renal fibrosis 40 .…”
Section: Discussionsupporting
confidence: 91%
“…TGF-causes mesangial enlargement due to mesangial cell hypertrophy, proliferation (and eventually apoptosis), and the production of extracellular matrix (ECM). It also causes endothelium to mesenchymal transition, which results in glomerular myofibroblasts, a significant source of ECM, to occur 50,51 . Current study showed a significant difference between male and female in ACE-2 levels.…”
Section: Groupsmentioning
confidence: 99%
“…Obesity is defined as an accumulation of mature adipocytes in adipose tissue. It is characterized by the increase in adipose tissue mass [1][2][3][4][5] due to the increase in adipocyte number…”
Section: Introductionmentioning
confidence: 99%